Effects of Azolla pinnata Compost and Carbonate Lime (CaCO₃) on Soil Chemical Properties, Nitrogen Uptake, and Yield Components of Sweet Corn Grown in Ultisols - Febri Yunarto; Bambang Sulistyo; Hasanudin Hasanudin; Esi Asyani Listyowati (TERRA : Journal of Land Restoration, 2025)
Ultisols, covering approximately 705,151 hectares in Bengkulu, represent a marginal soil type with considerable agricultural potential. However, they are limited by low nutrient availability, low pH, low organic carbon, and high concentrations of exchangeable aluminum (Al) and iron (Fe). These constraints significantly affect the growth and productivity of crops such as sweet corn, which is sensitive to acidic conditions and nutrient deficiency. Soil fertility improvement through organic matter application and liming is a promising approach. Azolla, an aquatic fern with high nitrogen content due to its symbiosis with Anabaena azollae, was used in composted form. This study aimed to determine the optimum application rates of Azolla compost and carbonate lime (CaCO₃) for improving nitrogen up take, growth, and yield of sweet corn in Ultisols. The treatments consisted of four Azolla compost levels (0, 5, 10, and 15 tons ha-1) and three lime rates equivalent to neutralizing 0, 1, and 2 units of exchangeable Al. A factorial experiment was arranged in a completely randomized design with three replications. Data were analyzed using analysis of variance (ANOVA), followed by orthogonal polynomial testing. Azolla compost significantly improved soil pH, organic carbon content, stem diameter, plant height, ear weight, biomass (fresh and dry), and nitrogen uptake. Lime applica tion significantly increased soil pH, stem diameter, and plant height. No significant interaction occurred between the two factors. Although positive responses were observed, the yield remained below the potential of the Bonanza F1 variety, likely due to high rainfall and suboptimal treatment levels. These findings support the integration of Azolla compost and lime into soil fertility management practices for sustainable sweet corn production on acidic tropical soils. Full text pdf